고기능 자폐스펙트럼장애 아동의 전제 의미 추론 - 윤송이(Song-ie Yoon); 황민아(Mina Hwang); 임종아(Jong Ah Lim) (특수교육논총, 2018)
연구목적: 전제는 진실이라고 가정하고 공유하는 배경지식이다. 본 연구는 고기능 자폐스펙트럼장애 아동이 문장에 전제된 의미를 추론하는데 어려움이 있는지 알아보고자 일반아동과 비교하여 조사하였다. 연구방법: 초등학교 1∼3학년 고기능 자폐스펙트럼장애 아동 9명과 생활연령을 일치시킨 일반아동 9명이 연구에 참여하였다. 아동들에게 사실적 전제와 함축적 전제로 구분된 총 32개의 전제문장과 판단문장을 듣고 참인지 거짓인지를 판단하게 하였다. 이렇게 얻어진 점수로 집단(2)×전제유형(2)의 이원 분산분석을 실시하였다. 연구결과: 고기능 자폐스펙트럼장애 아동은 일반아동에 비해 전제의미를 추론하는데 어려움을 보였으며, 사실적 전제와 함축적 전제유형에 따른 차이는 발견되지 않았다. 결론: 고기능 자폐스펙트럼장애 아동이 전제의미를 추론하는데 어려움이 있다는 것은 다양한 의사소통상황에서 주어진 전제에 기반한 정보교환에 어려움이 있을 수 있다는 것을 의미한다. 이러한 결과에 대해 선행연구들을 중심으로 추론과정, 작업기억 등과 관련하여 논의하였다. Purpose: The presupposition is a shared background assuming truth. The purpose of this study was to investigate comprehension difficulty in the presupposition meaning of sentences in children with high functioning Autism Spectrum Disorder(ASD). Methods: 9 children with high functioning ASD of 1st∼3rd grade elementary schools and 9 age matched typically developing children participated in the study. The children were asked to judge whether they were true or false by listening to a total of 32 pairs of sentences involved explicit and implicit presupposition. The repeated measures analysis of variance of group(2)× type(2) was performed with the obtained score. Results: Children with high functioning ASD had difficulty in drawing inference from the presuppositions of sentences than TD, and no difference was found between explicit and implicit presupposition types. Conclusion: The difficulty in drawing inference the presupposition in sentence of a children with a high-functioning ASD means that it may be difficult to exchange information based on a given presupposition in various communication situations. We discussed these results with the inference process, working memory. KCI Citation Count: 2